1995
DOI: 10.1074/jbc.270.25.15119
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD9 Monoclonal Antibody Activates p72 in Human Platelets

Abstract: NNKY 1-19, anti-CD9 monoclonal antibody (MoAb), induced protein tyrosine phosphorylation of 125-, 97-, 75-, 64-, and 40-kDa proteins in human platelets, whereas F(ab')2 fragments of NNKY 1-19 did not, suggesting that the stimulation of Fc gamma II receptors is required for the induction of protein tyrosine phosphorylation. Tyrosine-phosphorylated proteins of 97 and 125 kDa were associated with aggregation, while NNKY 1-19-induced protein tyrosine phosphorylation was completely inhibited by prostaglandin I2 (PG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…Like other tetraspanin proteins, CD9 has been known to be involved in signal transduction by forming complexes with integrins and other cell surface molecules including tetraspanin members (Maecker et al, 1997;Boucheix and Rubinstein, 2001;Yanez-Mo et al, 2001). In platelets, CD9 was shown to associate with some small GTP-binding proteins (Seehafer and Shaw, 1991) and CD9 ligation with anti-CD9 mAb increased p72syk-associated tyrosine kinase activity, along with cell aggregation (Ozaki et al, 1995). A recent report showed that the CD9 gene transduction downregulates Wnt signaling pathways in fibrosarcoma and lung cancer cells (Huang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Like other tetraspanin proteins, CD9 has been known to be involved in signal transduction by forming complexes with integrins and other cell surface molecules including tetraspanin members (Maecker et al, 1997;Boucheix and Rubinstein, 2001;Yanez-Mo et al, 2001). In platelets, CD9 was shown to associate with some small GTP-binding proteins (Seehafer and Shaw, 1991) and CD9 ligation with anti-CD9 mAb increased p72syk-associated tyrosine kinase activity, along with cell aggregation (Ozaki et al, 1995). A recent report showed that the CD9 gene transduction downregulates Wnt signaling pathways in fibrosarcoma and lung cancer cells (Huang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…So far there is no experimental evidence that one of these integrins is involved in CDV-induced cell-cell fusion. It has been reported that several signal transduction pathways are affected by antibodies against CD9 (30,31,47,48), that small G proteins are associated with CD9 (36), and that the binding activity of integrins is regulated by CD9 (23). Therefore, it is possible that antibodies to CD9 might regulate other proteins not identical with the directly associated integrins which may bind CDV or are involved in membrane fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-CD9 and anti-PETA-3 MAbs are able to induce platelet activation and mediator release by crosslinking of Fc ␥ RII, the low-affinity IgG receptor (Roberts et al 1995;Ashman et al 1991;Worthington et al 1990). More recent studies in platelets have demonstrated intrinsic signaling capacity for CD9, with anti-CD9 F(ab Ј ) 2 fragments inducing phosphorylation of the tyrosine kinase syk (Ozaki et al 1995). Signal transduction events have also been demonstrated in B-cells, granulocytes, and monocytes by anti-CD53 MAbs (Olweus et al 1993).…”
mentioning
confidence: 99%